Location markers to improve infrastructure maintenance / Nur Alya Maisarah Sanusi - Sanusi, Nur Alya Maisarah (2022)
This chapter provides the background and rationale for the study. It also gives details of the problem statement, project scope, objectives, and research significance that leads to this research.